Tracing aquatic resource contributions to Tree and Barn Swallow nestling diets across a cropland and wetland gradient - Ana Maria Diaz Bohorquez; Christy Morrissey; Keith A. Hobson (Avian Conservation and Ecology)
The nutritional quality of nestling diets, influenced by parental prey selection, determines offspring health and development. In agricultural landscapes, nestling diets may be impacted by changes in prey availability from agricultural intensification. In 2020 and 2021, we compared landscape-level effects on nestling prey resources in two sympatric species of breeding aerial insectivores, Tree Swallow ( Tachycineta bicolor ) and Barn Swallow ( Hirundo rustica ). Our study was conducted across an agricultural crop and wetland gradient in Saskatchewan, Canada. Using hydrogen stable isotope analyses (δ²H) of nestling feathers, as an indicator of differential diet composition of terrestrial vs. aquatic-emergent insects, we hypothesized that Tree Swallows, as aquatic insect specialists, would have lower feather δ²H values indicative of more aquatic diets. We predicted that increasing annual-row crop and wetland cover around nests would differentially impact each species with Tree Swallows being more sensitive to landscape differences given known reliance on wetland-derived prey. Wetland waters and select aquatic and terrestrial insects showed high variation presumably due to seasonal stochastic evaporation requiring greater sampling effort. However, evidence of differential use of aquatic resources was consistently found between the two swallow species and between wet versus dry years. Lower average Tree Swallow nestling feather δ²H values suggested their diet was more reliant on aquatic-emergent prey, unrelated to the land use around the nest (at 500–2000 m). In contrast, Barn Swallows had higher average feather δ²H, which decreased with greater standing water cover in proximity of the nest (< 500 m), suggesting more terrestrial diets with opportunistic use of aquatic-emergent prey resources. For both species, we found no effect of crop cover extent on the isotopic indicator of prey source. These results contribute to the growing body of evidence that multiple species of aerial insectivores rely on aquatic insect resources regardless of local agricultural land use. Our results highlight the importance of conservation of small, interspersed wetlands, especially in intensive cropland-dominated landscapes, to benefit multiple species of aerial insectivores.